Seagrass Community Structure in the Coastal Waters of Pandanan Sekotong Barat, West Lombok - Suryatni, Maulida; Santoso, Didik; Japa, Lalu (Jurnal Biologi Tropis, 2026)
Seagrass ecosystems play a crucial role in marine environments, particularly in supporting coastal biodiversity and maintaining ecological balance. The coastal waters of Pandanan Beach are ecologically vital but potentially exposed to anthropogenic pressures such as boat mooring and local foraging ("madak") activities. This study aimed to identify the species composition and analyze the community structure, including density, diversity, dominance, and coverage of seagrass in coastal waters at Pandanan Beach. Data collection were conducted using a quadrate transect method across three distinct transects. The results showed that a total of 7 seagrass species were identified, namely Cymodocea rotundata, C. serrulata, Enhalus acoroides, Halodule pinifolia, Halophila decipiens, Syringodium isoetifolium, and Thalassia hemprichii. The overall community structure of the seagrass was relatively stable and healthy, characterized by a mean total density of 163 ind/m² and an average canopy coverage of 52.28%. The species diversity index (H' = 1.65) fell into moderate category, supported by a low dominance index (D = 0.22), indicating an even distribution of species across the habitat. These findings suggest that despite ongoing human activities, the seagrass ecosystem in the coastal waters at Pandanan Beach remains in a resilient and healthy condition.